Host Innate Immune Responses Induced by Baculovirus in Mammals - Abe, Takayuki; Matsuura, Yoshiharu (Current Gene Therapy, 2010)
The baculovirus Autographa californica nuclear polyhedrosis virus has been widely used not only to achieve a high level of foreign gene expression in insect cells but also for efficient gene transduction into mammalian cells without any replication. In addition to the efficient gene delivery, baculovirus has been shown to induce host innate immune responses in various mammalian cells and in mice. The baculovirus has abundant CpG motifs in the viral genome and is capable of inducing pro-inflammatory cytokines and interferons through Toll-like receptor-dependent and -independent signaling pathways in a cell-type-specific manner. The baculovirus also has a strong adjuvant activity, and recombinant baculoviruses encoding neutralization epitopes elicit protective immunity in mice. This review deals with the current status of our knowledge of the induction of host innate immune responses by baculovirus and discusses the future prospects for baculovirus vectors.
Keywords: IFN